Point of Time and Effectiveness of Cause-Related Marketing: Strike While the Iron is Hot - Khuram Faraz; Dr. Abdul Aziz Khan Niazi; Usman Zafar; Usman Zafar (International Journal of Engineering and Management Research, 2020)
“Cause” is the word of positive-valence stimuli and increasing the like-hood intend to be a pair with it. Linking of consumer purchase with social cause is common and in rising trend. It’s a favorable tool of an organization to engage consumer and make his emotional attachment in charitable cause and increase sales volume. Previous Cause Related Marketing (CrM) literature has examined the CrM in term of consumer or in term of brand or purchase, we could not find any study which is investigating the mediating role of specific time between CrM and attitudes of consumers towards brand, ad, offer and cause involvement. Present study examines the best use of CrM according to time in beverages industry on soft drink on a holy occasion of Muslims (i.e. Ramazan). An already established questioner was used for collection of data. Mall intercept convenience technique is use to gather data. It’s a multiple group analysis study, data was collected two times, once during event and once after the event, sample size was remain same both times. Morgan’s formula is used to select the size of samples. Results of study show that CrM has influence on customer attitude which was being measured in three types, furthermore these attitudes has positively influence individual’s intention to buy a specific brand in a specific time period. This study will be provided a best use of CrM campaign according to time. Research will also direct the marketers to use of CrM on a specific time to tackle their customer’s attitude.